Fibrous nonwoven fabrics with improved wet strength, in particular paper, use of these wet strength fabrics and method for production thereof

By using wet strength agents of silicon components, such as silica and amino silica, the wet strength of fiber nonwoven fabrics is improved through impregnation technology, and the health and environmental problems existing in the papermaking process of existing wet strength agents are solved, achieving a more environmentally friendly and non-toxic wet strength improvement effect.

CN119768577APending Publication Date: 2025-04-04TECH UNIV DARMSTADT
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380060414.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-27
Filing Date
2023-07-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing wet strength agents have health problems and environmental pollution during the papermaking process, and are not conducive to waste paper recycling.

Method used

The wet strength of the fiber nonwoven fabric is improved by impregnation techniques using wet strength agents based on silicon components, such as silica and amino silica.

Benefits of technology

It achieves a more environmentally friendly and non-toxic wet strength improvement effect, improves the wet tensile strength of fiber nonwoven fabrics, and reduces the burden on the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768577A_ABST
    Figure CN119768577A_ABST
Patent Text Reader

Abstract

The present invention relates to novel environmentally friendly wet strength improved fibrous nonwoven fabrics, optionally paper, impregnated with a mixture comprising a silicon component, further comprising water and / or an alcohol and / or a surfactant and a catalyst. Methods of production and uses of such wet strength improved fibrous nonwoven fabrics are also included.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to an environmentally friendly fiber nonwoven fabric with improved wet strength, optionally paper, which is impregnated with a mixture containing a silicon component, water and / or alcohol and / or a surfactant and a catalyst (e.g., acidic or alkaline). It also includes a production method and use of such a fiber nonwoven fabric with improved wet strength. Background Art

[0002] Germany consumes a large amount of paper every year. In 2019, the per capita consumption was 227 kg. This corresponds to a total consumption of 18.9 million tons in Germany alone.

[0003] Paper is essentially a sheet or web of fibrous nonwoven fabric (usually cellulose fibers) to which chemicals are added to improve its properties and quality. In addition to fibers and chemicals, the production of pulp and paper requires large amounts of process water and significant amounts of energy in the form of steam and electricity. Therefore, the major environmental issues associated with the pulp and paper industry relate to water and air emissions and energy consumption. Waste is also an increasing source of environmental pollution.

[0004] Pulp for papermaking is produced by chemical or mechanical processes from virgin fibers or by processing waste paper.

[0005] Untreated paper becomes mechanically unstable when it becomes damp or wet. The fiber fleece loses its internal cohesion due to the breaking of hydrogen bonds when water enters.

[0006] In order to retain mechanical strength (albeit limited) even when wet, wet strength agents such as polyamidoamine epichlorohydrin (PAAE) are added to the paper during production. Tear-resistant kitchen crepe paper is probably the best-known of this type of paper, but cardboard, map paper, tea bags or banknote security paper also contain large amounts of wet strength agents.

[0007] Wet strength agents known in the prior art are water-soluble polymers which react with themselves and / or with the paper fibers in the processing state. In the process, water-insoluble crosslinks are formed between the fibers, which stabilize the fiber web.

[0008] The prior art describes industrially established wet strength agents based on melamine and urea-formaldehyde resins and polyamidoamine-epichlorohydrin (PAAE). These commercially used wet strength agents are formed from toxic starting substances and are based on petrochemical materials, which at least partly still remain in the final product. Therefore, there are particular health problems in papermaking, and the environmental input of these polymers (or their precursors) in wastewater and paper treatment cannot be satisfactorily avoided and represents a considerable environmental burden. The chemical connection also hinders successful recycling, so that the increasing use of wet strength agents in the field of toilet paper has a profound impact on waste paper recycling. For example, during the normal dissolution process, the incidence of insoluble particles is steadily increasing.

[0009] If conventional wet strength agents (similar to asphalt binders) are chemically broken down, the fibers degrade abnormally quickly. As a result, the quality of recovered paper decreases more rapidly than in a normal recycling process.

[0010] Wet strength agents must not be confused with sizing chemicals (such as AKD) because the chemical-physical processes of action are different. For example, wet strength degummed paper is still highly capillary, and strong glued paper can only be degummed after prolonged contact with water.

[0011] Another disadvantage of existing wet strength agents is that some develop their full wet strength only after a certain storage time, which is of course not profitable.

[0012] The present invention solves the above environmental problems by providing a more environmentally friendly fibrous nonwoven fabric, optionally paper, having improved wet strength, which is impregnated with a wet strength agent based on silicon components such as silica (SiO2) and aminosilica (SiO2-NH2). Summary of the invention

[0013] In a first aspect, the present invention is directed to a fibrous nonwoven fabric having improved wet strength, having an air-dried silica content of about 0.05 wt % or more, 0.1 wt % or more, 0.5 wt % or more, 1 wt % or more, or about 2 wt % or more, or about 5 wt % or more, or about 10 wt % or more; up to about 30 wt % or less, or up to about 25 wt % or less, or up to about 20 wt % or less; in one embodiment, between 1 wt % and 30 wt %, or between 2 wt % and 25 wt %, or between 5 wt % and 20 wt %.

[0014] In one embodiment, a low silica content between 0.05 and 5 wt% is preferred as it improves the economics of the process. As explained below, the silica content is related to the wet strength and composition of the impregnation solution.

[0015] Wherein the silica is uniformly distributed in the wet strength fiber nonwoven fabric, so that the silica content on one side of the wet strength fiber nonwoven fabric is less than a 2: 1 ratio with the silica content on the other side of the wet strength fiber nonwoven fabric, or less than a 1.5: 1 ratio, or less than a 1.25: 1 ratio, or about a 1: 1 ratio. Such distribution can be measured, for example, by IR spectroscopy of each surface and calculating the silica content of each surface and the ratio between the silica content, respectively.

[0016] and wherein the Cobb value of the fiber nonwoven fabric with improved wet strength after silica impregnation is compared to that of the untreated fiber nonwoven fabric. 60The Cobb value is reduced by about 20% or less. In one embodiment, the Cobb value is reduced by about 20% or less compared to the untreated fiber nonwoven fabric. 60 The value is reduced by about 10% or less, or by about 5% or less, or is about the same. "Cobb 60 The "value" is defined and measured according to DIN EN ISO 535 (2014-06-00) and describes the value of 1m after 60 seconds. 2 The amount of water absorbed by a material (in grams).

[0017] The term "untreated fibrous nonwoven web" refers to the same fibrous nonwoven web, but which has not been impregnated with any of the impregnation solutions disclosed in this application and / or otherwise treated with silica.

[0018] In another embodiment, the specific surface area measured by BET is about ±10%, or about ±5%, or about ±2% compared to the untreated fiber nonwoven fabric. "BET" or "BET" (Brunauer-Emmett-Teller) theory is intended to explain the physical adsorption of gas molecules on solid surfaces and is the basis of an important analytical technique for measuring the specific surface area of ​​a material. It is defined and measured according to DIN ISO 9277. The fiber nonwoven fabric with improved wet strength of the present invention shows a surface and pore distribution and size similar to that of the untreated fiber nonwoven fabric, thereby having the beneficial effect of maintaining the same water retention and / or permeability.

[0019] Without being bound by theory, it seems that the swelling capacity of the fibers in the fiber nonwoven fabric is slightly reduced by silica treatment, and this effect increases the improved wet strength. Swelling in water is one of the important basic properties of fibers in fiber nonwoven fabrics, and can be measured by drying rate. Experimentally, this method is very simple-a fiber sample that is fully swollen and contains excess water is dried very slowly and weighed regularly. The results show that over a period of time, moisture is lost at an almost constant rate. However, the drying rate eventually changes and then steadily decreases. It is believed that this change occurs only after all non-swelling water outside the fiber evaporates. The moisture recovery at this transition point of the drying rate is considered to be an indication of the maximum water holding capacity (i.e., swelling capacity) of cellulose. Therefore, in one embodiment, compared with untreated fiber nonwoven fabrics, the swelling capacity of the fiber nonwoven fabric with improved wet strength after silica impregnation is reduced by about 20% or less, or by about 10% or less, or by about 5% or less, or by about 2% or less, or by about 1% or less.

[0020] The fiber nonwoven fabric with improved wet strength of the present invention can be made of any nonwoven fabric made of short fibers (short) and long fibers (continuous long) bonded together by chemical, mechanical, thermal or solvent treatment. The term "nonwoven fabric" is used hereinafter to indicate a fabric that is neither woven nor knitted, such as felt. Some nonwoven materials lack sufficient strength unless densified or enhanced by a backing. In an important embodiment, the fiber nonwoven fabric is paper.

[0021] According to DIN ISO 3781, the fiber nonwoven fabric with improved wet strength of the present invention shows excellent wet tensile strength. Therefore, in one embodiment, compared with untreated fiber nonwoven fabric, the wet tensile strength according to DIN ISO 3781 of the fiber nonwoven fabric with improved wet strength of the present invention is about 2 times or more, or about 3 times or more, or about 5 times or more, or about 10 times or more. In another embodiment, compared with untreated fiber nonwoven fabric, the wet tensile strength is at most about 50 times or less, or at most about 35 times or less, or at most about 30 times or less, or at most about 25 times or less. In one embodiment of the present invention, compared with untreated fiber nonwoven fabric, the wet tensile strength is at least 2 times to at most 30 times, or at least 2.5 times to at most 25 times, or at least 3 times to at most 20 times, or at least 4 times to at most 15 times.

[0022] In one embodiment, the absolute wet strength of the improved fiber nonwoven fabric of the present invention is between 1 and 50 N / 15 mm, or between 2 and 40 N / 15 mm, or between 3 and 35 N / 15 mm, or between 4 and 30 N / 15 mm according to DIN ISO 3781 (1994-10).

[0023] In some embodiments, the wet strength improved fiber nonwoven fabric is still wettable and can absorb water. This is important because many applications of wet strength improved nonwoven fabrics are used to absorb water, such as kitchen towels (e.g., made of paper), tissue paper and / or handkerchiefs, etc., or still need to be permeable to water, such as tea bags or coffee filters.

[0024] Wettability can be quantified by the "contact angle," which is typically measured when a liquid-vapor interface meets a solid surface (e.g., a water droplet on a fibrous nonwoven fabric in air). It quantifies the wettability of a liquid to a solid surface via Young's equation.

[0025] Therefore, the contact angle of the surface of the wet strength improved fiber nonwoven fabric according to the present invention is less than 100°, or less than 90°, or less than 75°, or less than 60° on at least two main sides or all sides of the wet strength improved fiber nonwoven fabric.

[0026] In another aspect, the present invention relates to a wet strength improving impregnation solution comprising a silicon component for increasing the wet tensile strength of a fibrous nonwoven fabric, thereby producing an environmentally friendly and non-toxic final product, in particular paper and paperboard, wherein the impregnation solution further comprises an acidic catalyst, water and / or an alcohol, i.e. a compound having at least one hydroxyl functional group (-OH) bonded to a saturated carbon atom and conforming to the general formula C n H 2n+1 An organic compound of OH (e.g., ethanol, 1-propanol, 2-propanol, 2-methylpropan-1-ol, 2-methylbutan-2-ol and / or methanol), and / or a surfactant. Surprisingly, in some embodiments, some alkaline catalysts may produce nanoparticles instead of silica coatings, and therefore, these embodiments cannot be used as wet strength improving impregnations. Therefore, such mixtures are excluded from the present application. However, by checking for the absence of nanoparticles, the technician can identify alkaline catalysts that do form coatings and are therefore suitable for the impregnation solutions of the present application.

[0027] In one embodiment, the wet strength improving impregnation solution comprises tetraethyl orthosilicate (TEOS) as a "silicon component" for increasing the wet tensile strength of a fiber nonwoven fabric, particularly paper, wherein the impregnation solution further comprises water, ethanol (EtOH) as an alcohol and / or SDS (in the case of anionic surfactants) or CTAB (in the case of cationic surfactants) as a surfactant, and is preferably carried out under acidic or alkaline conditions. In the case of an "acid catalyst", hydrochloric acid (HCl) can be used.

[0028] Therefore, in another embodiment, the present invention also relates to a wet strength improving impregnation mixture (option II) comprising the following compounds in wt %:

[0029] Compound weight% Silicon components, such as tetraethyl orthosilicate (TEOS) 3.5-16 Surfactants (such as sodium lauryl sulfate or cetrimonium bromide) 0.2-1.5 <![CDATA[H2O]]> 80-95 (make up to 100%) Acid catalyst (such as HCl) 0.005-0.05

[0030] In one embodiment, the present invention also relates to a wet strength improving impregnation mixture (option II) comprising the following compounds in weight %:

[0031] Compound weight% Silicon components, such as tetraethyl orthosilicate (TEOS) 7-16 Surfactants (such as sodium lauryl sulfate or cetrimonium bromide) 0.5-1.5 <![CDATA[H2O]]> 80-95 (make up to 100%) Acid catalyst (such as HCl) 0.015-0.04

[0032] Therefore, in another embodiment, the present invention also relates to a wet strength improving impregnation mixture (option II) comprising the following compounds in wt %:

[0033] Compound weight% Silicon components, such as tetraethyl orthosilicate (TEOS) About 14.3 Surfactants (such as sodium lauryl sulfate or cetrimonium bromide) Approx. 1.0 <![CDATA[H2O]]> About 85 (to be replenished to 100%) Acid catalyst (such as HCl) About 0.03

[0034] In this regard, it is surprisingly found that cationic surfactants are significantly more effective than anionic surfactants in improving the wet strength of fibrous nonwoven fabrics. Therefore, although anionic surfactants selected from the group consisting of alkyl carboxylates, alkylbenzene sulfonates, secondary alkyl sulfonates, fatty alcohol sulfates (e.g., sodium lauryl sulfate, SDS), alkyl ether sulfates, sulfoacetates, and taurates may also be used in some embodiments, in preferred embodiments, cationic surfactants selected from the group consisting of: Formula R4N + tetraalkylammonium salts of quaternary ammonium salts (which differ in their alkyl residues (e.g. stearyl-, palmityl-, methyl-, benzyl-, butyl-), for example DSDMAC (distearyldimethylammonium chloride) and / or esterquats), benzalkonium chloride, benzethonium chloride, hexadecyldimethylbenzylammonium chloride, cetylpyridinium chloride, hexadecyltrimethylammonium bromide (cetrimonium bromide) and / or dequalinium chloride.

[0035] In one embodiment, an emulsifier selected from the following list may be added: ascorbyl palmitate (E 304), lecithin (E 322), sodium phosphate (E 339), potassium phosphate (E 340), propylene glycol alginate (E 405), salts of edible fatty acids (E 405), mono- and diglycerides of fatty acids (E 471), acetates of mono- and diglycerides of fatty acids (E 472a), lactic acid esters of mono- and diglycerides of fatty acids (E 472b), citric acid esters of mono- and diglycerides of fatty acids (E 472c), tartaric acid esters of mono- and diglycerides of fatty acids (E 472d), monoacetyltartaric acid esters and diacetyltartaric acid esters of mono- and diglycerides of fatty acids (E 472e), mixed tartaric acid esters and acetates of mono- and diglycerides of fatty acids (E 472f), sugar esters of fatty acids (E 472g). 473), sugar glycerides (E474), polyglycerol esters of fatty acids (E 475), polyglycerol polyricinoleate (E 476), propylene glycol esters of edible fatty acids (E477), (non-ionic): polysorbate 80 (E433) and polysorbate 60 (E435), polysorbate 65 (E436), polysorbate 40 (E 434), polysorbate 20 (E 432), pectin (E 440), carrageenan (E 407) and gum arabic (E414), and any combination thereof.

[0036] In yet another embodiment, other natural emulsifiers selected from the following list may be added: beeswax, glycerin, sorbitan derivatives (typically sorbitan esters) and / or non-ionic emulsifiers such as Ceteareth (polyoxyethylene ether) or PEG (polyethylene glycol) derivatives, and combinations thereof.

[0037] In yet another embodiment, an additional emulsifier selected from the following list may be added: styrene-maleic anhydride copolymer (SMA), styrene-butadiene latex (SBR), polyvinyl acetate (PVA), carboxymethyl cellulose (CMC), and wax emulsions, and combinations thereof.

[0038] In yet another embodiment, an additional emulsifier selected from the list of modified starches, such as sodium starch octenylsuccinate (E 1450), monostarch phosphate (E 1410), distarch phosphate (E1412), phosphorylated distarch phosphate (E 1413), acetylated distarch phosphate (E 1414) and acetylated starch (E1420), and any combination thereof, may be added as an emulsifier / stabilizer.

[0039] In yet another embodiment, an additional emulsifier selected from the following list may be added: sodium hydroxy-octadecane sulfonate, sodium, potassium and ammonium salts of hydroxy fatty acids with a chain length of C12-C20 and their sulfated or acetylated products, alkyl sulfates (also triethanolamine salts), alkyl (C10-C20) sulfonates, alkyl (C10-C20) aryl sulfonates, dimethyl dialkyl (C8-C18) ammonium chloride (not more than 0.005% based on the dispersed film), acyl, alkyl, oleyl and alkyl aryl oxyethylates and their sulfated products, sulfosuccinic acid 4-ester with polyethylene glycol nonylphenyl ether (disodium salt), lignin sulfonic acid and its calcium, magnesium, sodium and ammonium salts (not more than 0.04 mg / dm in total). 2 ), sodium dodecyl diphenyl ether disulfonate, copolymer of ethylene oxide and propylene oxide with a minimum content of 10%, ethylene oxide, lecithin (not more than 1 mg / dm 2 ), disodium 4-[1-methyl-2-[(1-oxo-9-octadecenyl)amino]ethyl]-2-sulfosuccinate (not more than 0.8 mg / dm 2 ), 4-sulfosuccinate (disodium salt) of polyethylene glycol ether with aliphatic monohydric alcohol of chain length C10-C12 (the transfer to food or food simulants shall not exceed 2 mg / kg), dicyclohexyl sulfosuccinate (sodium salt) (the transfer to food or food simulants shall not exceed 5 mg / kg), alkali metal salts of sulfosuccinates with aliphatic saturated monohydric alcohols of chain length C4-C20 (the transfer to food or food simulants shall not exceed 5 mg / kg).

[0040] The advantageous effect of cationic surfactants can be used in two different improved embodiments: to increase the wet strength of the impregnated fibrous nonwoven compared to mixtures containing anionic surfactants, or to reduce the amount of silicon component such as TEOS required for the impregnation solution, thereby reducing costs.

[0041] Therefore, in another embodiment, the present invention also relates to a wet strength improving impregnation mixture (option II) comprising the following compounds in wt %:

[0042] Compound weight% Silicon components, such as tetraethyl orthosilicate (TEOS) 1.75-8 Cationic surfactants (e.g., cetrimonium bromide) 0.2-1.5 <![CDATA[H2O]]> 80-95 (make up to 100%) Acid catalyst (such as HCl) 0.005-0.05

[0043] In one embodiment, the present invention also relates to a wet strength improving impregnation mixture (option II) comprising the following compounds in weight %:

[0044] Compound weight% Silicon components, such as tetraethyl orthosilicate (TEOS) 3.5-8 Cationic surfactants (e.g., cetrimonium bromide) 0.5-1.5 <![CDATA[H2O]]> 80-95 (make up to 100%) Acid catalyst (such as HCl) 0.015-0.04

[0045] Therefore, in another embodiment, the present invention also relates to a wet strength improving impregnation mixture (option II) comprising the following compounds in wt %:

[0046] Compound weight% Silicon components, such as tetraethyl orthosilicate (TEOS) Approx. 7 Cationic surfactants (e.g., cetrimonium bromide) About 1.0 <![CDATA[H2O]]> About 85 (to be replenished to 100%) Acid catalyst (such as HCl) About 0.03

[0047] In another embodiment, the present invention also relates to a wet strength improving impregnation mixture (Option I) comprising the following compounds in weight %:

[0048] Compound weight% Silicon components, such as tetraethyl orthosilicate (TEOS) 2-20 <![CDATA[H2O]]> 6-10 Alcohol (e.g. EtOH) 75-90 Acid catalyst (such as HCl) 0.001-0.05

[0049] Therefore, in another embodiment, the present invention also relates to a wet strength improving impregnation mixture (option I) comprising the following compounds in wt %:

[0050] Compound weight% Silicon components, such as tetraethyl orthosilicate (TEOS) 5-18 <![CDATA[H2O]]> 6-10 Alcohol (e.g. EtOH) 75-90 Acid catalyst (such as HCl) 0.01-0.04

[0051] Therefore, in another embodiment, the present invention also relates to a wet strength improving impregnation mixture (option I) comprising the following compounds in wt %:

[0052]

[0053]

[0054] Therefore, in another embodiment, the present invention also relates to a wet strength improving impregnation mixture (option I) comprising the following compounds in wt %:

[0055] Compound weight% Silicon components, such as tetraethyl orthosilicate (TEOS) About 17.1 <![CDATA[H2O]]> About 7.4 Alcohol (e.g. EtOH) Approx. 75.5 Acid catalyst (such as HCl) About 0.03

[0056] Additional compositions can be found in the Examples section.

[0057] In yet another embodiment, the present invention also relates to a fibrous nonwoven fabric obtained by impregnating the fibrous nonwoven fabric with one or more of the mixtures disclosed below.

[0058] In certain preferred embodiments, the impregnation solution consists of a silicon component. In other words, the proportion of the silicon component in the impregnation solution is 100% by weight. Thus, in particular, the impregnation solution can be pure silane. In other preferred embodiments, in addition to the silicon component, the impregnation solution also contains at least one further component, such as a solvent component, such as alcohol or water and / or an acid component. In further embodiments, a surfactant (such as SDS) may also be present in the solution.

[0059] In one embodiment, the proportion of the silicon component in the impregnation solution is in the range of 5 wt % to 100 wt %, or 10 wt % to 99 wt %, or 20 wt % to 98 wt %, or 40 wt % to 97 wt %, or 60 wt % to 96 wt %, or 80 wt % to 95 wt %.

[0060] In one embodiment, the silicon component is selected from the group consisting of tetraethyl orthosilicate (TEOS), tetramethyl orthosilicate, polydimethoxysiloxane, 1,2-bis(triethoxysilyl)ethane, tetraacetic silicon, (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine, [3-(2-aminoethylamino)propyl]trimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-(2-aminoethylamino)propyldimethoxymethylsilane, bis[3-(trimethoxysilyl)propyl]amine, and mixtures of two or more thereof. The component TEOS is particularly preferred. TEOS is a common base chemical that is inexpensive and readily available. In one embodiment, the component is pre-condensed (i.e., still liquid). The term "pre-condensed" means that only oligomers have been formed, but the material has not yet been fully polymerized.

[0061] In one embodiment, the impregnation solution contains a solvent in a proportion ranging from 0 to 98 wt%, or 0.1 to 50 wt%, or 0.2 to 20 wt%, or 0.5 to 10 wt%, or 1 to 5 wt%. In one embodiment, the solvent is selected from the group consisting of water, ethanol, and a mixture of two or more thereof. In one embodiment, the solvent is water.

[0062] In one embodiment, the impregnation solution contains water in a proportion ranging from 0 to 20 wt %, or 0.5 to 10 wt %, or 1 to 5 wt %.

[0063] In one embodiment, the impregnation solution contains an acid, such as HCl (37 wt%), in a proportion of 0.001 to 0.2 wt%, or 0.005 to 0.1 wt%, or 0.01 to 0.05 wt%.

[0064] In one embodiment, the impregnation solution according to the invention consists of at least 95% by weight, or at least 98% by weight, or at least 99% by weight, or at least 99.9% by weight, or at least 99.99% by weight of ethanol, water, silicon component and HCl. A particular advantage of the method according to the invention is that no additional components are required in the impregnation solution. In one embodiment, the impregnation solution even consists of at least 95% by weight, or at least 98% by weight, or at least 99% by weight, or at least 99.9% by weight, or at least 99.99% by weight of water, silicon component and HCl.

[0065] In one embodiment, the impregnated fiber nonwoven fabric comprises 0.1 to 30 wt % or 0.5 to 10 wt % or 1 to 5 wt % or 1.5 to 7.5 wt % of a silicon component (e.g. silicon dioxide or aminosilicon dioxide). In one embodiment, the impregnated fiber nonwoven fabric is composed of a fiber component (particularly paper) and an impregnating component (SiO 2 ).

[0066] In one embodiment, the impregnated fiber nonwoven fabric contains the fiber component in a proportion of 90 wt % to 99.9 wt %, or 92.5 wt % to 99.8 wt %, or 95 wt % to 99.5 wt %.

[0067] In one embodiment, the fiber nonwoven fabric of impregnation of the present invention is composed of fiber component (for example paper) and impregnation component (for example SiO ).The fiber nonwoven fabric may contain other components, or however, its ratio is at most 50 weight %, for example 0 to 30 weight %, or at most 25 weight %, or at most 10 weight %, or at most 5 weight %, or at most 2 weight %, or at most 1 weight %, or less than 0.5 weight %.These other components can especially be inorganic and / or organic fillers.

[0068] In one embodiment, the ratio of the fiber component and the impregnated component in the fiber nonwoven fabric of the present invention is at least 50 weight %, or at least 75 weight %, or at least 90 weight %, or at least 95 weight %, or at least 98 weight %, or at least 99 weight %.In one embodiment, the impregnated fiber nonwoven fabric of the present invention is composed of the fiber component and the impregnated component.

[0069] In one aspect, the present invention relates to a method for producing the wet strength improving impregnation solution of the present invention, comprising the following steps

[0070] a. Mix 10-20 mL TEOS (1 equivalent) with 20-40 μL HCl (37 wt %); and

[0071] b. stirring the mixture at 18-25 ° C for 12-48 hours; and

[0072] c. Add water to make the total liquid reach 100mL and 0.5-3g sodium dodecyl sulfate (SDS); and

[0073] d. stirring the mixture at 18-25°C for 0.5-3 hours;

[0074] e. thereby obtaining a wet strength improving impregnation solution in the form of an emulsion;

[0075] f. Optionally, adding at least one additional excipient selected from the group consisting of a thickener (eg, carboxymethylcellulose), a biocide, and a preservative, and any combination thereof.

[0076] In another embodiment, the present invention relates to a method for producing a wet strength improving impregnation solution comprising the steps of

[0077] a. 15.2 mL TEOS (1 equivalent) was mixed with 28 μL HCl (37 wt %); and

[0078] b. stirring the mixture at 20°C for 24 hours; and

[0079] c. Add 84.8 mL of water and 1 g of sodium dodecyl sulfate (SDS); and

[0080] d. stirring the mixture at 20°C for 1 hour;

[0081] e. A wet strength improving impregnation solution is thereby obtained in the form of an emulsion.

[0082] In yet another embodiment, the present invention relates to a method for producing a wet strength improved mixture, comprising the steps of

[0083] a. Mix 0.5-5 mol% tetraethyl orthosilicate (TEOS): 20-50 mol% EtOH: 5-20 mol% H2O: 0.005-0.1 mol% HCl (37 wt%),

[0084] b. Stir at room temperature for 24 hours,

[0085] c. A wet strength improving impregnation solution is thereby obtained in the form of a coating sol.

[0086] In yet another embodiment, the present invention relates to a method for preparing a wet strength improved mixture, comprising the steps of

[0087] a. Mix 1 mol% tetraethyl orthosilicate (TEOS): 40 mol% EtOH: 10 mol% H2O: 0.02 mol% HCl (37 wt%),

[0088] b. Stir at room temperature for 24 hours,

[0089] c. A wet strength improving impregnation solution is thereby obtained in the form of a coating sol.

[0090] In yet another embodiment, the present invention relates to any silica coated fibrous nonwoven fabric, optionally paper, obtained by coating the paper with any of the wet strength improving impregnation solutions mentioned below.

[0091] In one aspect, a fibrous nonwoven fabric, optionally paper, is obtained by coating the paper with a wet strength improving impregnation solution comprising 12-20 mL TEOS (1 equivalent), 10-45 μL HCl (37 wt %), 80-88 mL water (made up to 100 mL total liquid) and 0.25-3 g sodium dodecyl sulfate (SDS).

[0092] In yet another embodiment, a fibrous nonwoven fabric, optionally paper, is obtained by coating paper with a wet strength improving impregnation solution comprising 10-20 mL TEOS (1 eq), 15-40 μL HCl (37 wt%), 70-85 mL water and 0.5-2 g sodium dodecyl sulfate (SDS).

[0093] In yet another example, a fibrous nonwoven fabric, optionally paper, is obtained by coating paper with a wet strength improving impregnation solution comprising 15.2 mL TEOS (1 equivalent), 28 μL HCl (37 wt %), 84.8 mL water and 1 g sodium dodecyl sulfate (SDS).

[0094] In yet another embodiment, a fibrous nonwoven fabric, optionally paper, is obtained by coating paper with a wet strength improving impregnation solution comprising 0.5-3 mol % tetraethyl orthosilicate (TEOS): 20-60 mol % EtOH: 5-30 mol % H2O: 0.001-0.2 mol % HCl (37 wt %).

[0095] In yet another embodiment, a fibrous nonwoven fabric, optionally paper, is obtained by coating the paper with a wet strength improving impregnation solution comprising 1-2 mol % tetraethyl orthosilicate (TEOS): 30-50 mol % EtOH: 10-20 mol % H2O: 0.01-0.05 mol % HCl (37 wt %).

[0096] In yet another embodiment, a fibrous nonwoven fabric, optionally paper, is obtained by coating the paper with a wet strength improving impregnation solution comprising 1 mol % tetraethyl orthosilicate (TEOS): 40 mol % EtOH: 10 mol % H2O: 0.02 mol % HCl (37 wt %).

[0097] The invention also relates to a method for producing a fiber nonwoven fabric with uniform silica impregnation, in particular a fiber nonwoven fabric of the invention as described above. The invention also relates to a fiber nonwoven fabric with uniform silica impregnation, which can be obtained or has been obtained by the method.

[0098] In one embodiment, the impregnation solution may have been added to the bath containing the fibers of the fibrous nonwoven fabric before the production and drying of the fibrous nonwoven fabric itself. The advantage of this method is that the impregnation solution is evenly distributed on all fibers and the process is simplified. However, a disadvantage may be that a higher volume of impregnation solution is required, and therefore, an impregnation solution with a cationic surfactant is preferred.

[0099] Then, the method comprises the following steps:

[0100] a) obtaining an impregnation solution, wherein the wet strength improving impregnation solution contains a silicon component,

[0101] b) adding the impregnation solution to a bath also comprising fibers of the fibrous nonwoven fabric;

[0102] c) extracting the fibrous nonwoven fabric from a bath comprising fibers of the fibrous nonwoven fabric,

[0103] d) drying the fibrous nonwoven fabric at a temperature in the range of 4°C to 250°C.

[0104] In another embodiment, the fibrous nonwoven is impregnated later during the drying process.

[0105] The method comprises the following steps:

[0106] a) providing a fibrous nonwoven fabric,

[0107] b) obtaining an impregnation solution, wherein the wet strength improving impregnation solution contains a silicon component,

[0108] c) impregnating the fibrous nonwoven fabric with the wet strength improving impregnation solution,

[0109] d) drying the fibrous nonwoven fabric at a temperature in the range of 4° C. to 250° C.,

[0110] There is a time period of at most 60 seconds between the completion of the impregnation according to step c) and the start of the drying according to step d).

[0111] In one aspect, a method for producing silica coated paper comprises the following steps

[0112] a. Providing a fibrous nonwoven fabric, optionally paper;

[0113] b. obtaining a wet strength improving impregnation solution as described below;

[0114] c. applying the coating mixture to at least one side of the paper, optionally evenly to both sides, with a size press at a speed between 1 and 15 m / min and a roll pressure between 0.25 and 3.0 bar;

[0115] d. The paper is heated from 18-25°C to 60-200°C at a heating rate between 5-15K / min at a constant air flow between 15-50mL / min;

[0116] e. Thereby obtaining a fibrous nonwoven fabric, optionally paper, having improved wet strength.

[0117] In one embodiment, the method for producing silica coated paper comprises the following steps

[0118] a. Providing a fibrous nonwoven fabric, optionally paper;

[0119] b. obtaining a wet strength improving impregnation solution as described below;

[0120] c. applying the coating mixture to at least one side of the paper, optionally evenly to both sides, with a size press at a speed of about 5 m / min and a roller pressure between 0.5 and 1.0 bar;

[0121] d. heating the paper from 18-25°C to 60-200°C at a heating rate between 5-15K / min at a constant air flow between 15-50mL / min;

[0122] e. Thereby obtaining a fibrous nonwoven fabric, optionally paper, having improved wet strength.

[0123] The advantages of the product and the method described according to the invention compared to the prior art are an environmentally friendly, non-toxic end product (i.e. containing only SiO2), which also allows technical applications of the fiber nonwoven fabrics with improved wet strength according to the invention in the food industry. In addition, the impregnation can be carried out at below 150°C (between 4-40°C; or an ambient temperature of 20°C) and atmospheric pressure, which leads to significant energy savings. Moreover, since the impregnation works so quickly, the paper can be further processed in the production line quite quickly. Furthermore, since a uniform distribution is preferred, a "zigzag" arrangement of contact elements and / or rollers can be used to dry the paper evenly from both sides.

[0124] According to step a) of the method of the present invention, a fiber nonwoven fabric is provided. In one embodiment, the fiber nonwoven fabric is selected from the group consisting of nonwoven paper fabric, nonwoven textile fabric and nonwoven plastic fabric. In one embodiment, the fiber nonwoven fabric is a nonwoven paper fabric. In one embodiment, the nonwoven paper fabric provided has a weight of 10-1000 g / m 2 In one embodiment, the weight is 10-20 g / m 2 or 12-15g / m 2 In other embodiments, the grammage is between 250-1050 g / m 2 or 300-1000g / m 2 In another embodiment, the grammage is 65 to 120 g / m 2 , or 70 to 100 g / m 2 , or 75 to 90 g / m 2 .

[0125] The fiber nonwoven fabric can be a commercially available fiber nonwoven fabric. In particular, the nonwoven paper fabric can be a commercially available nonwoven paper fabric. In an alternative embodiment, the step of providing a fiber nonwoven fabric, in particular a nonwoven paper fabric, can also include the step of producing a fiber nonwoven fabric, in particular a nonwoven paper fabric. In one embodiment, during sheet forming In one embodiment, the apparatus is carried out according to DIN 54358 and / or ISO 5269 / 2 (ISO5269-2:2004(E), "Pulps - Preparation of laboratory sheets for physical testing - Part 2: Rapid Methods, 2004”), optionally with Method for producing nonwoven paper fabric.

[0126] In some embodiments, in the production of fiber nonwoven fabrics, particularly nonwoven paper fabrics, no additional additives or fillers are used. In other embodiments, additives such as preservatives, bleaching agents, thickeners, etc. may be used.

[0127] According to step b) of the method of the invention, an impregnation solution containing a silicon component is provided. In the present specification, the terms "impregnating solution" and "impregnation solution" are used in a synonymous sense. The impregnation solution may be a single-component solution and may therefore consist of one single component. In this case, the impregnation solution may also be specifically referred to as an "impregnating fluid" or "impregnation fluid".

[0128] After the addition of the individual components, the impregnation solution is optionally stirred for a period of 6 to 48 hours, or 12 to 36 hours, or 18 to 30 hours, and then the impregnation of the fiber nonwoven fabric, in particular the nonwoven paper fabric, with the impregnation solution is carried out according to step c) of the method of the invention. In embodiments of the invention in which the impregnation solution consists of a silicon component, in particular TEOS, in one embodiment, no such stirring is carried out.

[0129] Step c) of impregnating the fibrous nonwoven fabric, in particular the nonwoven paper fabric, with the impregnation solution is optionally carried out at a relative air humidity in the range of 10% to 95%, or 30% to 70%, or 40% to 60%, or 45% to 55% and / or at a temperature in the range of 15°C to 30°C, or 20°C to 25°C.

[0130] In one embodiment, impregnating the fiber nonwoven fabric with the impregnation solution is by exposing the fiber nonwoven fabric to the impregnation solution, therefore in other words, by contacting the fiber nonwoven fabric with the impregnation solution to realize.For the design of this step that the fiber nonwoven fabric is contacted with the impregnation solution, there are many possibilities.In one embodiment, impregnating the fiber nonwoven fabric with the impregnation solution according to the step c of the method is realized by the impregnation method selected from the group consisting of: film coating, matching coating, dip coating, spraying, size press, roller coating, blade coating and curtain coating.Dip coating and spraying are especially preferred.Particularly preferably dip coating.In one embodiment, the impregnation solution is evenly distributed on the surface and inside of the fiber nonwoven fabric.

[0131] According to an embodiment of the present invention, the impregnation in step c) of the present invention is realized by immersing the fiber nonwoven fabric in the impregnation solution. In one embodiment, the fiber nonwoven fabric, particularly the nonwoven paper fabric is fully immersed in the impregnation solution. In one embodiment, impregnation is carried out so that the fiber nonwoven fabric, particularly the nonwoven paper fabric is basically vertically oriented. In other words, vertical orientation refers to that the two main surfaces of the fiber nonwoven fabric are arranged so that the surface vector orthogonal to the main surface is basically horizontally oriented. In one embodiment, the surface vectors of the two main surfaces and the vector of the immersion direction each form an angle of at least 70 ° and at most 110 °, or at least 80 ° and at most 100 °, or at least 85 ° and at most 95 °.

[0132] In one embodiment, the fiber nonwoven fabric is taken out from the impregnation solution at a time point of 0.1 to 10 seconds or 1 to 5 seconds after the fiber nonwoven fabric is immersed in the impregnation solution. The minimum and maximum time of contact with the impregnation solution also depends on the production process: in the case of impregnation by an impregnation process, up to 30 seconds, up to 1 minute, up to 5 minutes are still acceptable, and in the case of a size press system, contact is much shorter, between 0.1 seconds and 5 seconds. However, contact should not be significantly less than 0.05 seconds, nor should it exceed 30 minutes.

[0133] In one embodiment, the fiber nonwoven fabric is taken out from the impregnation solution so that the fiber nonwoven fabric is basically vertically oriented. In other words, vertical orientation refers to that the two main surfaces of the fiber nonwoven fabric are arranged so that the surface vectors orthogonal to the main surface are basically horizontally oriented. In one embodiment, the surface vectors of the two main surfaces and the vector of the take-out direction each form an angle of at least 70 ° and at most 110 °, or at least 80 ° and at most 100 °, or at least 85 ° and at most 95 °.

[0134] According to step d) of the inventive method, the drying of the fiber nonwoven fabric is carried out at a temperature in the range of 70°C to 190°C. In one embodiment, the drying of the fiber nonwoven fabric is carried out at a temperature in the range of 80°C to 180°C, or 90°C to 170°C, or 100°C to 160°C, or 110°C to 150°C, or 120°C to 140°C, or 125°C to 135°C. In one embodiment, the drying of the fiber nonwoven fabric according to step d) is carried out until the residual moisture content of the fiber nonwoven fabric is in the range of 3% by weight to 7% by weight. In one embodiment, the residual moisture content is determined by gravimetric analysis, in particular according to DIN EN20287. At higher temperatures, the pulp of the paper may be affected and show discoloration.

[0135] There is a time period of at most 60 seconds, or at most 45 seconds, or at most 30 seconds, or at most 20 seconds, or at most 10 seconds, or at most 5 seconds, or at most 2 seconds, or at most 1 second between the completion of the impregnation according to step c) and the start of the drying according to step d). In one embodiment, the drying according to step d) of the method of the present invention is carried out immediately after the fibrous nonwoven fabric is impregnated with the impregnation solution according to step c) of the method, in other words directly.

[0136] In one embodiment, the impregnation according to step c) is completed when the fiber nonwoven fabric is no longer exposed to the impregnation solution, or in other words, when the fiber nonwoven fabric is no longer in contact with the impregnation solution. In the case of dip coating, for example, the impregnation according to step c) is optionally completed when the fiber nonwoven fabric is completely removed from the impregnation solution again, for example, pulled out of the impregnation solution. In the case of spraying, for example, when the impregnation solution is no longer sprayed onto the nonwoven fabric, the impregnation according to step c) is optionally completed.

[0137] Drying according to step d) optionally starts when the fibrous nonwoven fabric enters an environment designed to remove moisture and / or condensation products, such as an oven.

[0138] It is presumed that in the short period between the completion of the impregnation and the start of the drying, when drying is effected at an elevated drying temperature, the silicon component of the impregnation solution is still not converted to a significant extent into the silicate component of the silica impregnate. This allows the homogeneity of the silica impregnate to be adjusted in a targeted manner. Since the silicon component migrates through the nonwoven fabric at elevated drying temperatures, which depend on the drying conditions, in particular the ambient pressure, it is sufficient that it is not converted into a silica impregnate with a high degree of polymerization.

[0139] In embodiments where the impregnation solution contains no solvent, the migration of the silicon component through the fiber nonwoven fabric at elevated drying temperatures can be influenced in particular by adjusting the ambient pressure during drying. In embodiments where the impregnation solution contains a solvent, the migration of the silicon component can also be influenced in particular by evaporation of the silicon component and / or the solvent at elevated drying temperatures, since the silicon component migrates through the fiber nonwoven fabric together with the solvent.

[0140] As the polymerization proceeds further, the fluidity in the fiber nonwoven fabric decreases further. Thus, when there is a longer period of time after the impregnation of the fiber nonwoven fabric with the impregnation solution until the start of drying at elevated temperature, and therefore when the period of time between steps c) and d) of the method is relatively long, this leads to a significant polymerization before the relevant migration of the silicon component through the fiber nonwoven fabric occurs. This leads to obtaining a fiber nonwoven fabric with a uniformly distributed silicon dioxide impregnation, since the distribution of the already polymerized coating is no longer influenced by the drying conditions at elevated drying temperatures.

[0141] In contrast, the method according to the invention is designed such that a time period of at most 60 seconds is provided between the completion of the impregnation according to step c) and the start of the drying according to step d). Thus, at the start of drying, no substantial polycondensation has yet occurred, so that the silicon components present in the impregnation solution migrate through the fiber nonwoven and thus the distribution of the silicon dioxide impregnation can be influenced in a targeted manner by migration.

[0142] In one embodiment, drying is achieved with the help of a dryer. In one embodiment, the dryer is selected from the group consisting of a hot air / convection dryer, an oven, a drum dryer (contact drying) and an IR dryer. For example, it can be dried in an oven, or in a drying oven (in some embodiments a vacuum oven) or in a muffle furnace. In one embodiment, the oven / drying device is preheated, in particular to the drying temperature, so that after the impregnation according to step c), the drying according to step d) can be started very quickly. However, in one embodiment, the dryer is a hot air dryer.

[0143] According to the present invention, the characteristic of the fiber nonwoven fabric that is obtained can not only be subject to the influence of the above-mentioned method steps, and particularly can also be subject to the influence of the main environmental pressure during the drying period.Surprisingly found that SiO in the fiber nonwoven fabric The distribution of content can be controlled in a targeted manner by the pressure conditions during the drying period.Have relatively high SiO at two major surfaces The fiber nonwoven fabric of content can especially obtain under low pressure.

[0144] In one embodiment, according to step d) pressure during the drying period in the scope of 0.1kPa to 500kPa or 0.2kPa to 200kPa. In some preferred embodiments, according to step d) pressure during the drying period in the scope of 0.1kPa to 30kPa or 0.2kPa to 20kPa or 0.5kPa to 10kPa or 10kPa to 5kPa. Such embodiment is particularly suitable for producing such fiber nonwoven fabric, wherein SiO content is relatively high at two major surfaces, yet relatively low (so-called sandwich structure) at the center of the fiber nonwoven fabric. On the other hand, in other preferred embodiments, according to step d) pressure during the drying period in the scope of >30kPa to 500kPa or 50kPa to 200kPa or 60kPa to 150kPa or 70kPa to 130kPa or 80kPa to 120kPa or 90kPa to 110kPa. Such an embodiment is particularly suitable for producing a fiber nonwoven fabric in which the SiO2 content at one of the two main surfaces is significantly higher than at the other of the two main surfaces, while the SiO2 content at the center of the fiber nonwoven fabric is lower than at one of the two main surfaces, but higher than at the other of the two main surfaces. This is especially true when using an impregnation solution with a low or medium proportion of silicon components, in particular a proportion of silicon components in the range of 0.1 mol % to 3.5 mol %, or 0.2 mol % to 3 mol %, or 0.5 mol % to 2.5 mol %, or 0.9 mol % to 2.2 mol %.

[0145] In one embodiment, after drying, the fibrous nonwoven fabric is cooled to a temperature of 15°C to 30°C or 20°C to 25°C.

[0146] In one embodiment, the method consists of the steps mentioned. A particular advantage of the method according to the invention is that the method requires only a few steps to be carried out.

[0147] The invention also comprises paper having increased wet strength produced according to the method according to steps a) to d).

[0148] The invention also relates to the use of the fiber nonwoven according to the invention, in particular as packaging material.

[0149] Preferred uses as packaging material include use as freezer paper, for products that come into contact with food, such as, in particular, (paper) cups and / or (paper) straws, and as packaging for materials that prevent the ingress of liquids but should still allow moisture to diffuse. In particular, the fiber nonwoven fabrics of the invention can be used for plastic-free straws and / or cardboard cups. In view of possible regulations to reduce plastic waste, it can be assumed that the demand for plastic-free products will increase. Fiber nonwoven fabrics for the above-mentioned uses, in particular for drinking straws and cups, are often also referred to as specialty papers.

[0150] Other examples of suitable materials whose wet strength may be improved are tea bags, kitchen paper, cardboard, map paper, banknote security paper, coffee or tea filters, wrapping paper, toilet paper, paper towels, cooking paper, paper labels, display boards, promotional posters, corrugated board, paper bags and / or cloth, etc.

[0151] The present invention also relates to the use of the fiber nonwoven fabric according to the invention as special paper for use at elevated temperatures, in particular to the use of the fiber nonwoven fabric according to the invention as baking paper.

[0152] The invention also includes the use of the described wet strength agent for making a paper product having an increased relative wet strength of greater than 2%, greater than 5%, or greater than 10%, or greater than 15% as measured by the tensile elongation test according to ISO 1924-2.

[0153] In further embodiments, the paper is measured by tensile elongation strength according to ISO 1924-2 and achieves a relative wet strength greater than 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% and up to 31%, 32%, 33%, 34%, 35%, 40%, 50%.

[0154] The method for determining properties under tensile stress as specified in this part of ISO 1924-2 is one of the most commonly used methods. It is similar to the method specified in ISO 1924-3. In this part of ISO 1924 (ISO 1924-2), a constant strain rate of 20 mm / min is applied, while in ISO 1924-3, the constant strain rate is 100 mm / min.

[0155] Since the results of the tensile test depend on a constant strain rate, tests carried out according to this part of ISO 1924 and ISO 1924-3 will not give the same results. The dependence on speed may vary from paper grade to paper grade and therefore be different for the width-dependent breaking force, elongation at break, work absorption capacity and modulus of elasticity.

[0156] This international standard was developed by ISO / TC 6 "Paper, board and pulp" in cooperation with CEN / TC 172 "Fibrous materials, paper and board", whose secretariat is held by DIN. The National Committee for Material Testing (NMP) played an important role in the development of this standard. The national mirror committee is Joint Committee NA 062-04-26GA "Physical-technical test methods for paper and board". For the rest, we refer to the specifications in the corresponding DIN standards.

[0157] The fiber nonwoven fabric of the present invention is a fiber nonwoven fabric. In one embodiment, the fiber nonwoven fabric is selected from the group consisting of nonwoven paper fabric and nonwoven textile. In one embodiment, the fiber nonwoven fabric is a nonwoven paper fabric.

[0158] In one embodiment, the fibrous nonwoven fabric of the present invention has high flexibility.

[0159] Thus, in one embodiment, the paper mentioned below is selected from the group consisting of eucalyptus paper and / or northern bleached softwood kraft paper (NBSK). In other embodiments, cotton linters (80 g / m 2 ) and / or abaca (13g / m 2 Other papers that can be used according to the present invention include: Aburatorigami, Affiche paper, albumin paper, Alfapaper, Amatl, APCO II / II (DIN 16519T2), watercolor paper (120 g / m 2 Up to 850g / m 2 Between, from about 150g / m 2 Watercolor board), copy paper, backing paper, baking paper, banana paper, banknote paper, baryta paper, Bible printing paper (weight between 25 and 60 g / m 2between; also known as thin printing paper), illustration paper, blueprint paper, bombyzine paper, letter paper, stamp paper, book paper, colored paper, handmade paper, butter paper or parchment substitute, Chinese paper, Chinese rice paper, chromo paper, plate-making paper, decalcified paper, thick printing paper, document paper, double wax paper, printing paper, double paper, carbonless copy paper (also known as carbonless paper or copy paper, gram weight 30-40g / m 2 ), ice paper (ice paper or alabaster paper), elephant skin, electrical insulation paper, ivory paper, ivory board (weight 240 to 320g / m 2 ), continuous printing paper for EDP printing (DIN 672), label paper, fabriano paper, fine paper (paper completely free of groundwood but containing rags according to DIN), filter paper, felt paper, flocked paper (velvet paper), florpost (florpost paper), photographic paper, coated paper, ribbed paper or vergé paper, glass fiber paper, adhesive paper, rag paper (at least 10% rags or cotton, hemp or flax fibers), semi-chemical paper (at least 65% semi-chemical pulp in the total fiber pulp), hemp paper, hard paper (fiber composite material of paper and phenolic synthetic resin (phenoplast), hard post paper (also called bank post paper paper), high gloss paper (paper coated on one side but not calendered), groundwood paper (not more than 5% by weight of lignified fibers), groundwood paper (not less than 5% by weight of lignified fibers), hydrographic paper, toilet paper (especially crepe paper), Ingres paper (handmade paper or cylindrical mold handmade paper), Japanese paper, potassium iodide starch paper, chancery paper (weight 60 to 120 g / m 2 ), carbon copy paper, Khoi paper, copy paper, anticorrosive paper (VCI paper, volatile corrosion inhibitor), kraft paper, kraft paper (also known as: packaging paper) (weight before about 130g / m 2 , now about 80g / m 2), chalk paper, coloured crepe paper, kitchen crepe paper, powdered paper (art paper), plastic fibre paper or plastic paper, copper printing paper, map paper, leather paper, tracing paper, blotting paper (also known as nonwoven paper), manila paper, medical paper (ISO 11607, EN 868-6, EN 868-3 and ISO 10993-5), metallised paper, metal-laminated paper, medium-fine paper, mummy paper, natural fibre papers (these include papers made from cotton, banana, sisal, mulberry fibre, rice, corn, wheat straw paper, kudzu paper, daphne paper (Lokta, Nepal, Himalayan paper, Daphne bholua and Daphne papyracea), uncoated paper (uncoated paper with a maximum of up to 5 g / m 2 surface treatment or coloring), offset printing paper (also referred to as offset paper), oiled or waxed paper according to DIN 6730, parabaic, parchment substitute (also known as butter paper), parchment, parchment substitute (also known as greaseproof paper), parchment, poster paper, drawing paper, letter paper (post paper) (grammage between 70 and 120 g / m 2 ), quartz fiber paper (filter paper containing quartz fibers), swell paper, recycled paper (any paper containing more than 25% recycled paper before further refining), rice paper, base paper, saa paper (also called siam paper), absorbent paper, SC paper, silhouette paper (or clay paper) (weight 80-90g / m 2 ), sandpaper, writing paper, typewriter paper (also known as SM paper, DIN 6730), draft paper, swellpaper, thin crepe paper (weight 25g / m 2 ), carbonless copy paper (also called NCR paper) (no carbon required), anti-counterfeiting paper, silicone paper, tension paper, spider paper, spinning paper, stone paper, straw paper, synthetic paper, rope (or packaging rope, hanging rope), tea bag paper (mainly made of Manila abaca fiber), directory paper (about 35g / m 2 ), thermal paper, rotogravure paper, tracing paper, release paper, vellum (imitation vellum), velvet paper, wasli paper, watermark paper, work printing paper, rice paper, drawing paper (from 60g / m 2 different starting weights), newsprint, cigarette paper and combinations thereof.

[0160] The terms grammage or basis weight are used interchangeably herein.

[0161] Wet strength papers produced by the described process or wet strength agent are particularly suitable for applications which are naturally exposed to moisture but still require paper stability. Such papers are, for example, wrapping paper and cartons, banknote paper, handkerchiefs, kitchen crepe paper and cleaning cloths, cigarette paper, sandwich paper, newsprint, filter paper for, e.g., tea and coffee, etc.

[0162] In another aspect, the wet strength impregnating solution and the fiber nonwoven fabric and paper are also used in / as a product with improved wet tensile strength, the product being selected from the group comprising: tea bags, kitchen paper, cardboard, map paper, banknote security paper, coffee or tea filters, wrapping paper, toilet paper, thick paper towels, cooking paper, paper labels, display boards, promotional posters, drinking straws, wrapping paper, corrugated board, paper bags, cloth.

[0163] In one aspect of the present invention, the nonwoven material (e.g., paper) with improved wet strength can be particularly useful for food contact materials due to its non-toxic nature. This is important for paper cups, especially when holding hot beverages or food (e.g., instant soup cups), microwave pots or other dishes and / or tableware that come into contact with acidic and / or hot food or beverages, tea bags, coffee filters, paper straws, etc. In those cases, an aminosilica content of 0.7-1% is preferred.

[0164] In one embodiment, the mixture comprises the following compounds in wt %:

[0165] Compound weight% Organosilicon compounds (e.g., tetraethyl orthosilicate (TEOS)) 3.5-15 Surfactants 0.2-1.5 <![CDATA[H2O]]> 80-95 Acidic Catalyst 0.05-0.05

[0166] The term "air-dried" is a term known in the art and is used to describe additives added to porous materials such as fiber nonwoven fabrics. When describing the proportion of additives in "air-dried" porous materials such as fiber nonwoven fabrics, it refers to the state of the material with less than 10% by weight of residual moisture (e.g., water). This state can be achieved by drying the fiber nonwoven fabric under SATP conditions ("standard ambient temperature, pressure"), i.e. T = 298,15K (25°C); pressure (p) = 101.300Pa = 101,3kPa = 1,013 bar. "Oven-dried" is defined as the state of a porous material such as a fiber nonwoven fabric without any residual moisture, i.e., a residual moisture of 0% by weight. This can be achieved, for example, by drying the material for 15 minutes at a pressure (p) = 101.300Pa in a preheated oven at 160°C, but can also be achieved by other drying schemes in which the material is dried until no weight change can be measured.

[0167] Thus, "air dried" is a general term describing a porous material such as a fibrous nonwoven fabric having a residual moisture content of less than 10%, for example between 0% and 10%, whereas "oven dried" is the specific case of a porous material such as a fibrous nonwoven fabric having a residual moisture content of 0%. BRIEF DESCRIPTION OF THE DRAWINGS

[0168] Figure 1 : Schematic diagram depicting the double-sided coating process using a size press.

[0169] Figure 2 : Depicted are the thermogravimetric analyses of: a) model papers with different compositions of long fibers (LF; NBSK) and short fibers (SF; eucalyptus), namely 20LF80SF (black line), 50LF50SF (dashed line) and 80LF20SF (dotted line), coated with silica by option I, and b) coated with silica by option II.

[0170] Figure 3 : SEM micrographs of eucalyptus paper before (left) and after silica coating by Option I (middle) and Option II (right) are shown at a magnification of 2000. Scale bar, 10 μm.

[0171] Figure 4 : a) Wet tensile strength of model papers unmodified (black) and coated with silica using coating option I (grey) with different compositions of long fibers (LF; NBSK) and short fibers (SF; eucalyptus). b) Wet tensile strength of model papers unmodified (black) and coated with silica by coating option II (grey), and a reference (white) performed without silica source in the coating solution.

[0172] Examples

[0173] Reagents

[0174] Unless otherwise stated, all chemicals and solvents were purchased from Merck Millipore and Thermo Fisher Scientific and used as received.

[0175] Example 1. Preparation of paper

[0176] Laboratory engineered papers were produced using bleached eucalyptus kraft pulp and northern bleached softwood kraft (NBSK; pine and spruce) pulp. The pulp was refined in a 40 laboratory refiner at 75,000 rpm. According to DIN 54358 and ISO 5269 / 2, the The paper sheet forming machine produces a grammage of 80±1.6g / m 2Laboratory engineered paper. No additives or fillers were used. Model papers with different fiber ratios of long fiber (LF; NBSK) and short fiber (SF; eucalyptus) of 100LF:0SF (eucalyptus), 20LF:80SF, 50LF50SF and 80LF20SF were prepared.

[0177] In one embodiment, paper is prepared by mixing a paper fiber pulp suspension with an impregnation solution and subsequently drying the paper. For 20LF80SF used in the fiber suspension, a wet strength of 1.58 ± 0.1 N / 15 mm was achieved with an oven dried silica content of 1.28% and an air dried silica content of 1.22%.

[0178] Example 2. Silica coating

[0179] Option I: Dipping Sol

[0180] For silica coating of paper, a coating sol with the following composition was prepared (option I).

[0181] Very good results were obtained in terms of wet strength:

[0182] Compound Molar amount Volume (50mL) / mL Mass / g weight% TEOS 1 152.30 140.302356 17.07 <![CDATA[H2O]]> 5 60.66 60.6620971 7.38 EtOH 20 786.47 620.527963 75.51 HCl 0.01 0.56 0.24554428 0.03

[0183] Very good results were also obtained in terms of wet strength:

[0184] Compound Molar amount Volume (50mL) / mL Mass / g weight% TEOS 1 82.43 75.9336755 9.33 <![CDATA[H2O]]> 10 65.66 65.6624185 8.07 EtOH 40 851.30 671.677517 82.56 HCl 0.02 0.61 0.26578427 0.03

[0185] Still good results were obtained in terms of wet strength:

[0186] Compound Molar amount Volume (50mL) / mL Mass / g weight% TEOS 1 43.01 39.617674 4.90 <![CDATA[H2O]]> 20 68.52 68.5174864 8.47 EtOH 80 888.32 700.882731 86.63 HCl 0.01 0.16 0.06933521 0.009

[0187] Still mediocre results were obtained in terms of wet strength:

[0188] Compound Molar amount Volume (50mL) / mL Mass / g weight% TEOS 1 21.98 20.2466071 2.50 <![CDATA[H2O]]> 40 70.03 70.0317049 8.66 EtOH 160 907.95 716.372055 88.54 HCl 0.005 0.04 0.01771687 0.002

[0189] The components of the sol were mixed, stirred at room temperature for 24 hours, and applied using a size press ( Figure 1 ) for silica coating of paper by double-sided coating at a speed of 5 m / min at a roll pressure of 0.5-1.0 bar. The freshly coated paper was placed in a preheated oven at 160° C. for 5-15 minutes at atmospheric pressure and then cooled to ambient temperature.

[0190] Option II: Dipping Lotion

[0191] For silica coating of paper, a coating emulsion was prepared as follows (option II).

[0192] Very good results were obtained in terms of wet strength:

[0193] Compound V / mL m / g n / mol Molar Ratio weight% TEOS 15.2 14.288 0.06721183 1.00 14.29 <![CDATA[H2O]]> 84.8 84.6304 4.69777408 69.90 84.67 HCl 0.028 0.03318 0.00033671 0.01 0.03 SDS NA 1 0.00350208 0.05 1.00

[0194] Good results were obtained in terms of wet strength:

[0195] Compound V / mL m / g n / mol Molar Ratio weight% TEOS 15.2 14.288 0.06721183 1.00 7.15 <![CDATA[H2O]]> 184.8 184.4304 10.237602 152.32 92.33 HCl 0.028 0.03318 0.00033671 0.01 0.02 SDS NA 1 0.00350208 0.05 0.50

[0196] Average results were obtained in terms of wet strength:

[0197] Compound V / mL m / g n / mol Molar Ratio weight% TEOS 15.2 14.288 0.06721183 1.00 3.58 <![CDATA[H2O]]> 384.8 384.0304 21.3172578 317.17 96.16 HCl 0.028 0.03318 0.00033671 0.005 0.01 SDS NA 1 0.00350208 0.05 0.25

[0198] TEOS was mixed with HCl (37 wt%) and stirred at room temperature for 24 hours. Water and sodium dodecyl sulfate (SDS) were then added and the mixture was stirred vigorously at room temperature for 1 hour before applying the resulting emulsion for coating using a size press at a speed of 5 m / min at a roller pressure of 0.5-1.0 bar. The freshly coated paper was placed in a preheated oven at 160° C. for 5-15 minutes at atmospheric pressure and then cooled to ambient temperature.

[0199] Surprisingly, the wet strength of the model papers with different fiber ratios of long fibers (LFSF 20 / 80%; NBSK 100%) when the paper was treated with the mixture according to option II comprising the cationic surfactant cetrimide as surfactant was 23±4 N / 15 mm, i.e. much higher than the other impregnations.

[0200] Surprisingly, it was found that TEOS can be put into solution as an emulsion without the use of ethanol. Therefore, Option II shows some advantages over Option I. For example, EtOH (or alcohols in general) has safety risks (alcohol fumes, explosiveness) and is more expensive than water. Therefore, Option II is the preferred mixture for impregnation.

[0201] Example 3. Thermogravimetric analysis (TGA)

[0202] Using TGA 1 TGA was performed. The sample was heated from 25°C to 600°C at a heating rate of 10 K / min under a constant gas flow of 30 mL / min.

[0203] Example 4. Scanning Electron Microscopy (SEM)

[0204] A Zeiss EVO 10 was used operating at an accelerating voltage of 10 kV. SEM micrographs were recorded.Before the measurements, the samples were sputter coated with a 10 nm layer of platinum / palladium.

[0205] Example 5. Determination of wet tensile strength

[0206] In a controlled environment at 23°C and 50 RH%, using software from ZwickRoell GmbH & Co. Kg II V3.71, using a Zwick Z1.0 with a 1 kN load cell, the wet tensile strength was determined as the average of 10 samples in accordance with DIN ISO 3781. Therefore, the paper samples were immersed in water for at least 1 hour before the measurement.

[0207] Example 6. Determination of silicon dioxide content

[0208] The silica content of the silica coated papers was determined by TGA. Thus, the silica content can be determined from the plateau of the TGA curve at 550°C, since silica is stable up to 1700°C, while the natural organic fibers are completely burned. Comparing the values ​​between 550°C and 600°C before and after silica coating allows taking into account the natural ash content of the substrate. Furthermore, the weight loss occurring until 150°C can be attributed to physically adsorbed water and is taken into account in the calculation to determine the silica content relative to the oven-dried sample. The TGA curves of the model paper coated with silica by option I and the eucalyptus paper coated with silica by option II are shown in Figure 2 The calculated silica content is shown in Table 1.

[0209] Table 1: Calculated silica content from TGA.

[0210]

[0211] Example 7. Morphological analysis

[0212] The morphology of eucalyptus paper before and after silica coating was investigated using SEM ( Figure 3 ). The silica coated papers coated with Option I and Option II do not show morphological differences on a micrometer scale compared to the uncoated paper. This can be explained by the lower silica content inferred from the TGA.

[0213] Example 8. Determination of wet tensile strength

[0214] The wet tensile strength of paper before and after coating with silica was determined in accordance with DIN ISO 3781. Therefore, before the measurement, paper samples 15 mm wide and approximately 120 mm long were immersed in water for 1 hour. The wet tensile strength was determined as Figure 4As shown. Comparing the wet tensile strength before and after silica coating, higher values ​​were obtained for both Option I and Option II due to silica coating. Therefore, the wet tensile strength of the model paper coated with silica by Option I showed higher values ​​than that of the eucalyptus paper coated with silica by Option II. In addition, comparing the model papers with different compositions of long fibers and short fibers, the greater the number of short fibers (eucalyptus), the higher the wet tensile strength.

[0215] Example 9: Wet Strength Characteristics of Different Papers and Impregnation Mixtures

[0216] The wet strength of different papers and different mixtures was compared. As reference paper, a paper (asymmetrically impregnated with TEOS) was used, ie the silica content on one side was at least twice that on the other side.

[0217] In the case of impregnation with the mixture according to options I and II, a homogeneous silica distribution is applied, wherein the silica content on one side is about 2 times or less than on the other side.

[0218] The silica content is described in Table 1 of Example 6.

[0219] Table 2: Comparison of wet strength.

[0220]

[0221] Example 10: Contact angle measurement

[0222] Use from Contact angle measurements were performed using a TBU90E model from Instruments GmbH and SCA software. All samples were measured at five locations and the mean and standard deviation were calculated. Static contact angle measurements were performed using a drop volume of 2 μl (application rate: 0.5 μl / s) (at 23°C and 50% relative humidity).

[0223] Example 11: Comparison with prior art impregnation

[0224] Eucalyptus fiber paper with a grammage of 80 gsm was prepared in the laboratory. The paper was coated using a size press and an ethanol solution according to US2022 / 034041 and an aqueous emulsion and ethanol solution according to the present disclosure.

[0225] Table 3: Formulations of aqueous emulsions according to the present disclosure.

[0226] Compound V / mL m / g TEOS 15 14.1 <![CDATA[H2O]]> 385 385 HCl 0.028 0.033 CTAB NA 1

[0227] Table 4: Formulation of ethanol solutions according to the present disclosure.

[0228] Compound V / mL m / g TEOS 2.2 2.1 <![CDATA[H2O]]> 7 7 EtOH 90.8 71.6 HCl 0.004 0.005

[0229] Table 5: Formulation of ethanol solution according to US2022 / 034041

[0230] Compound V / mL m / g TEOS 33 31 <![CDATA[H2O]]> 26 26 EtOH 340 268.3 HCl 0.24 0.284

[0231] The paper was coated by a size press and subsequently dried in an oven. For the preparation according to US'041, the coated paper was placed in a preheated oven at 130°C for 15 minutes. To prepare wet strength paper with a silica coating according to the present disclosure, the coated paper was placed in a preheated oven at 160°C for 15 minutes.

[0232] After coating, the paper was equilibrated at 50% relative humidity and 23° C. The Cobb density of the two main sides of the coated paper was then determined according to DIN EN ISO 535. 60 Value. Weight is 80g / m 2 The uncoated paper made from eucalyptus fiber has a density of 310±37 g / m 2 Initial water absorption.

[0233] Table 6: Water absorption capacity of sponge cloths coated with different silica contents.

[0234]

Claims

1. A wet strength improved fibrous nonwoven fabric having an air-dried silica content of at least 0.1 wt. %, wherein the silica is distributed in the wet strength fibrous nonwoven fabric such that the ratio of the silica content on one side of the wet strength fibrous nonwoven fabric to the silica content on the other side of the wet strength fibrous nonwoven fabric is about 1:1, and wherein the Cobb ® silica content is 0.1 wt. % compared to an untreated fibrous nonwoven fabric. 60 The value decreased by less than 20%.

2. The wet-strength improved fibrous nonwoven fabric according to claim 1, wherein the fibrous nonwoven fabric is selected from the group consisting of paper and cotton linter.

3. A fiber nonwoven fabric with improved wet strength according to any one of claims 1 or 2, wherein the wet tensile strength of the fiber nonwoven fabric according to DIN ISO 3781 is at least 5 times to at most 50 times the wet tensile strength of the fiber nonwoven fabric according to DIN ISO 3781 without silicon dioxide content.

4. A fibrous nonwoven with improved wet strength according to any one of the preceding claims, wherein the wet tensile strength according to DIN ISO 3781 (1994-10) is between 1 and 50 N / 15 mm.

5. The wet strength-improved fibrous nonwoven fabric according to any one of the preceding claims, wherein the air-dried silica content is between at least 0.1 wt. % and at most 30 wt. %.

6. A fibrous nonwoven with improved wet strength according to any one of the preceding claims, wherein the contact angles on all surfaces of the fibrous nonwoven with improved wet strength according to the invention are less than 90°.

7. A fibrous nonwoven fabric with improved wet strength according to any one of the preceding claims, wherein the silica coated paper has a wet strength of 10 g / m2 according to DIN EN ISO 535 (2014). 2 and 300g / m 2 The water absorption capacity between.

8. A fibrous nonwoven fabric with improved wet strength according to any one of the preceding claims, obtained by impregnating the fibrous nonwoven fabric with a mixture comprising a silicon component, water, a surfactant and an acidic catalyst.

9. A mixture comprising the following compounds in % by weight: 。 10. The mixture according to claim 9, wherein the surfactant is a cationic surfactant.

11. A mixture comprising the following compounds in % by weight: 。 12. The fiber nonwoven fabric according to any one of the preceding claims 1 to 8, obtained by impregnating the fiber nonwoven fabric with the mixture according to any one of the preceding claims 9 to 11.

13. A process for producing a fibrous nonwoven fabric, optionally paper, having improved wet strength, comprising the steps of: a. obtaining a fiber nonwoven fabric; b. applying the impregnation solution according to any one of claims 9 to 11 uniformly to both sides of the paper at a speed between 1 and 15 m / min and a roller pressure between 0.25 and 3.0 bar; c. heating the paper from 18-25°C to 60-200°C at a heating rate between 5-15K / min at a constant air flow between 15-50mL / min; d. thereby obtaining the fibrous nonwoven fabric, optionally paper, having improved wet strength.

14. A process for producing a fibrous nonwoven fabric, optionally paper, having improved wet strength, comprising the steps of: a. The impregnation solution according to any one of claims 9 to 11 is mixed in a bath having fibers for the fibrous nonwoven fabric; b. extracting the fiber nonwoven fabric from the bath; c. heating the paper from 18-25°C to 60-200°C at a heating rate between 5-15K / min at a constant air flow between 15-50mL / min; d. thereby obtaining the fibrous nonwoven fabric, optionally paper, having improved wet strength.

15. Use of a fiber nonwoven with improved wet strength according to any one of claims 1 to 8 or an impregnation solution according to any one of claims 9 to 11 on a fiber nonwoven for producing an article with improved wet tensile strength, the article being selected from the group consisting of: tea bags, kitchen paper, cardboard, map paper, banknote security paper, coffee or tea filters, wrapping paper, toilet paper, paper towels, cooking paper, paper labels, display boards, promotional posters, straws, wrapping paper, corrugated board, paper bags, cloth.

Citation Information

Patent Citations

  • Asymmetrically silica-impregnated nonwoven fabrics and methods for producing said nonwovens and use thereof

    US20220034041A1